Competitiveness of Tea Exports in Asean: A Constant Market Share Analysis - Nadia Oktaviana; Masyhuri Masyhuri; Slamet Hartono (Jurnal Ilmu Pertanian, 2016)
This study was aimed to find out the competitiveness of tea exports in ASEAN during 2011-2014. Competitiveness indicates a country ability to compete with other countries in international trade activities. Constant Market Share (CMS) employed to understand the weaknesses and strengths of a country viewed from the effect of exports growth. CMS results showed that the major weakness of tea exports in Malaysia, Singapore, Thailand, and Vietnam is the effect of market distribution. Market distribution effect indicated that their exports to countries with a high demand for tea in the world. On the other hand, the strengths of tea exports in Malaysia, Singapore, Thailand, and Vietnam are the effect of world exports growth, commodity composition effect, and the competitiveness effect. Conversely, the major weakness of tea exports in Indonesia is competitiveness effect, while the strengths are the effect of world exports growth and the effect of market distribution.